Yield, Yield Components, and Nutritive Value of Perennial Forage Grass Grown under Supplementary Irrigation. (17th January 2022) - Faji, Mulisa; Kebede, Gezahagn; Feyissa, Fekede; Mohammed, Kedir; Mengistu, Gezahegn
Abstract : There is a distinct seasonality in the availability of feeds in the highlands of Ethiopia, reaching a peak and low levels towards the end of the rainy and dry season, respectively. Consequently, this trial was conducted to assess the yield performance and nutritive value of nine perennial grasses accessions from seven grass species under supplementary irrigation to produce feed year-round. The evaluated grasses species were two Urochloa ( U. decumbens cv. ILRI-10871 and ILRI-13205), two Setaria ( S. sphacelata cv. ILRI-143 and ILRI-6543), one Phalaris ( Phalaris aquatica cv. Sirrosa), coloured Guinea ( Panicum coloratum cv. Coloratum), Desho ( Pennisetum glaucifolium cv. Kindu kosha), Napier ( Pennisetum purpureum cv, ILRI-16791), and Rhodes ( Chloris gayana cv. Massaba) variety. The experiment was carried out in a randomized complete block design. The chemical compositions of the grasses were scanned by, the near infrared spectroscopy (NIRS). Results indicated that the plant height, dry matter, and crude protein yield were significantly affected by year, species (P < 0.001 ), and their interaction (P < 0.05 ). Moreover, species were significantly influenced in vitro dry matter digestible yield, relative feed value, and nutrient content (DM, CP, NDF, ADF, ADL, and IVDMD). Napier grass had superior in dry matter, crude protein, and in vitro dry matter digestible yield than the other perennial grasses species tested together. Thus, among the tested grasses species, Napier grass showed outstanding potential as a forage plant followed by Phalaris and Desho grass under supplementary irrigation in the central highland of Ethiopia.